Analytical approach for the design of flexural elements made of reinforced ultra‐high performance concrete. (13th May 2020) - Yao, Yiming; Mobasher, Barzin; Wang, Jingquan; Xu, Qizhi
Abstract: The increasing demands of sustainable design and construction with economical sections, reduced cover, and more efficient time schedule require more flexibility in the design methodologies. The development of ultra‐high performance concrete (UHPC) have gained increasing interests as an attractive option for structural members with lightweight and superior performances. Concrete members reinforced with steel bars and fibers, generally known as hybrid reinforced concrete (HRC), offer a feasible solution in terms of reducing reinforcing materials and achieving desired structural performance. This paper proposes an analytical model to predict the flexural behavior of hybrid reinforced UHPC with steel reinforcements. Moment–curvature solutions are derived for reinforced sections based on parameterized tension‐compression constitutive models. The approach is applicable to customized cross section and derivation of T‐section is demonstrated. The moment–curvature response is further simplified as a tri‐linear model, which is used for the development of full‐range displacement solutions in analytical form. The proposed model is validated with the experimental data from literature covering a range of materials and member sizes. The full‐range solutions may provide insights into the serviceability design approach based on the criterion of maximum crack width or allowable deflection.